The determinants of motivation regarding top competitive basketball of juniors - Šimková, K.; Válková, H. (Studia Sportiva, 2019)
The motivation plays an essential role in carrying out any activity in people´s lives. It is a critical aspect between individual stages of career transitions and its goals. The purpose is to describe the determinants of the motivation and adherence of junior basketball players. The research interviews 40 players who wish to continue at the professional stage. The Career Transition theory (Alfermann & Stambulova, 2007) is a scope for the research. The research is qualitative, using The Grounded Theory by Strauss and Corbin (1990). The chosen research instrument was a semi-structured interview. The sample consists of twenty girls and twenty boys between ages 15-18. The results illustrate eight determinants of motivation and adherence. 1. lifestyle, 2. the perception of competencies, 3. specifics of basketball, 4. biopsychosocial health. 5. enjoyment, 6. team spirit, 7. society, 8. time management. Time management is the most occurring reason for termination of the basketball career.